Optimization of the SiC powder source size distribution for the sublimation growth of long crystals boules - Steiner, Johannes; Arzig, Matthias; Hsiao, Ta Ching; Wellmann, Peter (Materials Science Forum, 2019)
The influence of four different SiC source powder size distributions on the sublimation behavior during physical vapor transport growth of SiC was studied. The growth processes were carried out in a 3 inch crystal growth setup and observed in situ using advanced 3D computed tomography X-ray visualization. The single modal D90 size distribution of two source powders was 50 µm and 200 µm, respectively, with a corresponding average powder density of 1.17 g/cm³. The third source powder consisted of a blend of the previously named powders and exhibited an average powder density of 1.66 g/cm³ with a bimodal particle size distribution. The last source was composed of a solid polycrystalline SiC cylinder. The bimodal powder source exhibited a smoother morphology change and material consumption during the growth run and led to a much more stable shape change of the growth interface compared to the single modal source powders. The solid source featured the least morphology change. Therefore, with a careful adaption of the source material stable growth conditions can be achieved.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Computed tomography; In-situ visualization; Physical vapor transport; Silicon carbide; Source material